Loneliness, sociability, and life satisfaction of selcted elderly in Barangay Pagsanghan, Banga, Aklan. - Teodosio, Hazel Geanne Rocio (2017.)
This is a descriptive study aimed to determine the loneliness, sociability and life satisfaction of selected elderly in a barangay. Thirty (30) respondents, ages 60 years old and above were chosen as respondents of the study. The study utilized UCLA Loneliness Scale and Life Satisfaction Index and an interview guide to determine the causes of loneliness and sociability of the elderly. It was found out that the respondents have low level of loneliness and the highest causes of their loneliness are social isolation and being away from their family the respondents involved themselves in the barangay activities and maintain a satisfying interpersonal relationship with people in the barangay. Family is the source of their support and happiness. Their life satisfaction level is average.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Elders; Loneliness -- Elderly; Sociability -- Elderly; Life satisfaction -- Elderly